Enhancing Effectiveness in Teaching and Learning Technical Drawing for Sustainable Development in Nigerian Technical Colleges - Oke, J. O.; Olakotan, O. O. (INVOTEC, 2019)
This study determined enhancing effectiveness in teaching and learning technical drawing for sustainable development in Nigerian technical colleges. Two research questions focusing on status of Technical Drawing in Nigerian Technical Colleges and mechanisms for enhancing teaching and learning of Technical Drawing guided the study. The population of the study was all the 152 technical college administrators in state government owned technical colleges in South- Western States of Nigeria. A 30-item self-developed questionnaire was used to collect data from all the 152 respondents. The questionnaire was validated by three experts and its reliability coefficient was established at 0.92 using Cronbach’s Alpha Coefficient method. The data collected were analyzed using descriptive statistics. The study found that traditional mode of classroom instruction dominated the teaching and learning of technical drawing and that procurement of ICT facilities and retraining of technical drawing teachers would enhance teaching and learning of the subject. The study recommended, among others that relevant stakeholders responsible for the administration of technical colleges should procure ICT facilities for teaching and learning of technical drawing.